Couple's Narratives of Communion and Isolation Following Abnormal Prenatal Microarray Testing Results. (December 2016) - Werner-Lin, Allison; Barg, Frances K.; Kellom, Katherine S.; Stumm, Kallyn J.; Pilchman, Lisa; Tomlinson, Ashley N.; Bernhardt, Barbara A.
In 2% to 3% of cases, prenatal microarray testing detects deletions and duplications in a fetus' genome that are undetected by conventional cytogenetics. Many of these changes are associated with variable or uncertain symptomatology. Little is known about how couples experience uncertain results. This study analyzed 24 interviews with members of 12 heterosexual U.S. couples who received pathogenic or uncertain microarray prenatal testing results. Researchers used narrative analysis to examine couples' understanding and incorporation of findings into decision making regarding pregnancy termination. Couples felt unprepared for these findings and frustrated because scant information was available to aid interpretation. Women sought information and made decisions, and men marginalized their distress to support their wives. A shift in voice from first to second person indicated attempts to normalize emotional responses by making the process "common" to all couples. Families pursuing highly sensitive prenatal testing may need expert guidance to support decision making.